2022
DOI: 10.1371/journal.pone.0274049
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of knowledge and adherence to COVID-19 safety protocols among nurses at health facilities in Tamale Metropolis of Northern Ghana

Abstract: Background Corona Virus Disease of 2019 (COVID-19) emerged in 2019 and caused widespread disruption to many facets of life, including healthcare. Healthcare workers, particularly nurses, became the front-line fighters against the pandemic, making it imperative to comply with recommended safety protocols. However, many nurses were infected by the virus in the Tamale Metropolis, raising concerns regarding their level of adherence to the safety protocols. This study assessed the predictors of knowledge and adhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Few studies in Ghana have assessed IPC practices among HCWs amidst the COVID-19 pandemic. 20 , 23 25 About 9.1–80.8% adherence to IPC practices during the COVID-19 pandemic was reported among HCWs in Ghana. 20 , 23 , 25 Ashinyo et al 23 reported that non-clinical staff had 57.0% reduced risks of adherence to hand hygiene compared to clinical staff.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies in Ghana have assessed IPC practices among HCWs amidst the COVID-19 pandemic. 20 , 23 25 About 9.1–80.8% adherence to IPC practices during the COVID-19 pandemic was reported among HCWs in Ghana. 20 , 23 , 25 Ashinyo et al 23 reported that non-clinical staff had 57.0% reduced risks of adherence to hand hygiene compared to clinical staff.…”
Section: Introductionmentioning
confidence: 99%
“… 20 , 23 25 About 9.1–80.8% adherence to IPC practices during the COVID-19 pandemic was reported among HCWs in Ghana. 20 , 23 , 25 Ashinyo et al 23 reported that non-clinical staff had 57.0% reduced risks of adherence to hand hygiene compared to clinical staff. Abatanie et al 25 in their study found that about 60.2% of HCWs had adequate knowledge of COVID-19 safety protocols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation